2001
DOI: 10.1385/bter:81:3:215
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and Diabetes Mellitus Is There a Need of Zinc Supplementation in Diabetes Mellitus Patients?

Abstract: Diabetes mellitus is a group of metabolic disorders, the incidence of which varies widely throughout the world. The treatment of diabetes mellitus includes insulin, oral antidiabetic agents, and dietary regimens. Although the emphasis is on macronutrients intakes, there is strong evidence that there is an abnormal metabolism of several micronutrients in diabetic individuals. Zinc is one of the essential micronutrients of which status and metabolism is altered in this condition. This work is a short review abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 45 publications
1
60
0
5
Order By: Relevance
“…Alzheimer's Disease (AD) and Type 2 Diabetes (T2D) are closely related to each other as both exhibit common metabolic disorders including zinc [90], [91] and insulin degrading enzyme (IDE) deficiencies [30], [35]. Mittal et al [56] has also suggested that AD is a neuroendocrine disorder and that IDE could be the major player which possesses the ability to shift T2D to other metabolic pathways such as regulation of amyloid beta degradation by IDE.…”
Section: Clinical Impact Of Insulin Degrading Enzyme (Ide) On Alzheimmentioning
confidence: 99%
“…Alzheimer's Disease (AD) and Type 2 Diabetes (T2D) are closely related to each other as both exhibit common metabolic disorders including zinc [90], [91] and insulin degrading enzyme (IDE) deficiencies [30], [35]. Mittal et al [56] has also suggested that AD is a neuroendocrine disorder and that IDE could be the major player which possesses the ability to shift T2D to other metabolic pathways such as regulation of amyloid beta degradation by IDE.…”
Section: Clinical Impact Of Insulin Degrading Enzyme (Ide) On Alzheimmentioning
confidence: 99%
“…With Cu, Zn plays an important role in improving the condition of OS state as a cofactor for superoxide dismutase (35). Low values of Zn in diabetic patients can be explained by an alteration of the intestinal absorption of Zn and an increase in urinary excretion, since high concentrations of Zn in urinary secretion are often reported in diabetic patients (36). The Cu/Zn ratios were higher in diabetic patients compared to controls.…”
Section: Discussionmentioning
confidence: 96%
“…Согласно исследованиям последних лет, ряд неорганических соединений, например, соли ванадия [8], молибдена [9], хрома [10], цинка [11] обладают выраженным инсулиномиметическим действием [12][13][14][15]. На данный момент соединения ванадия, которым посвящен обзор, рассматриваются как потенциальные средства, которые позволят уменьшить инсулинорезистентность, не повышая дозу инсулина при СД 1 типа, увеличить чувствительность тканей к инсулину и усилить его эффекты при СД 2 типа.…”
Section: * -адресат для перепискиunclassified